Quantification of the zymogenicity and the substrate-induced activity enhancement of complement factor D - Dani, Ráhel; Oroszlán, Gábor; Martinusz, Róbert; Farkas, Bence; Dobos, Bernadett; Vadas, Evelin; Závodszky, Péter; Gál, Péter; Dobó, József (Frontiers in Immunology, 2023)
Complement factor D (FD) is a serine protease present predominantly in the active form in circulation. It is synthesized as a zymogen (pro-FD), but it is continuously converted to FD by circulating active MASP-3. FD is a unique, self-inhibited protease. It has an extremely low activity toward free factor B (FB), while it is a highly efficient enzyme toward FB complexed with C3b (C3bB). The structural basis of this phenomenon is known; however, the rate enhancement was not yet quantified. It has also been unknown whether pro-FD has any enzymatic activity. In this study, we aimed to measure the activity of human FD and pro-FD toward uncomplexed FB and C3bB in order to quantitatively characterize the substrate-induced activity enhancement and zymogenicity of FD. Pro-FD was stabilized in the proenzyme form by replacing Arg25 (precursor numbering) with Gln (pro-FD-R/Q). Activated MASP-1 and MASP-3 catalytic fragments were also included in the study for comparison. We found that the complex formation with C3b enhanced the cleavage rate of FB by FD approximately 20 million-fold. C3bB was also a better substrate for MASP-1, approximately 100-fold, than free FB, showing that binding to C3b renders the scissile Arg-Lys bond in FB to become more accessible for proteolysis. Though easily measurable, this cleavage by MASP-1 is not relevant physiologically. Our approach provides quantitative data for the two-step mechanism characterized by the enhanced susceptibility of FB for cleavage upon complex formation with C3b and the substrate-induced activity enhancement of FD upon its binding to C3bB. Earlier MASP-3 was also implicated as a potential FB activator; however, MASP-3 does not cleave C3bB (or FB) at an appreciable rate. Finally, pro-FD cleaves C3bB at a rate that could be physiologically significant. The zymogenicity of FD is approximately 800, i.e., the cleavage rate of C3bB by pro-FD-R/Q was found to be approximately 800-fold lower than that by FD. Moreover, pro-FD-R/Q at approximately 50-fold of the physiological FD concentration could restore half-maximal AP activity of FD-depleted human serum on zymosan. The observed zymogen activity of pro-FD might be relevant in MASP-3 deficiency cases or during therapeutic MASP-3 inhibition.